Fluorescence from a single Symbiodinium cell. (12th April 2018) - Guzman, Christine; Han, Xue; Shoguchi, Eiichi; Chormaic, Síle Nic
Abstract: The partnership between coral and its algal symbionts, Symbiodinium, is crucial to the global environment. Yet, the regulatory process within the photosynthetic machinery of Symbiodinium is still not clearly understood. Here, we studied the influence of light stress from focussed red and blue lasers on single Symbiodinium cells. Fluorescence signals were measured to show cell response. Increasing the incident laser power or the exposure time resulted in an increase followed by a decline in fluorescence intensity. The trend of fluorescence intensity changes was associated with mechanisms of light use efficiency, non-photochemical quenching, photoinhibition, and repair of the cell. Our study provides new approaches to studying the photobiology and physiology of Symbiodinium cells.